Gambling and the use of credit: an individual and household level analysis - Sarah Brown; Andy Dickerson; Jolian McHardy; Karl Taylor (Institute for the Study of Labor (IZA), 2010)
We explore the relationship between gambling and other forms of risk-taking behaviour, i.e. exposure to debt and the use of credit, at the individual and household level using representative pooled cross-section data drawn from the UK Expenditure and Food Surveys (EFS), 2001 to 2007. Gambling and the use of credit are shown to be positively correlated at the household level. While both the incidence and amount of gambling vary according to household income, the positive association between gambling and the use of credit is remarkably stable across household income. In addition to our household level analysis, we also explore the prevalence of intra-household gambling, which has attracted relatively limited attention in the existing literature. It is apparent that there is strong intra-household correlation in both gambling activity and in the use of credit, with somewhat stronger relationships in lower income households.
Keywords: D14; D81; L83; 330; Risk-taking; gambling; credit; debt; Risikopräferenz; Glücksspiel; Kredit; Private Verschuldung; Schätzung; Großbritannien